Factors affecting student adjustment as they transition from primary to secondary school: a longitudinal investigation - Vaz, Sharmila Maria Agnella (Curtin University, 2010)
Transition from primary to secondary school occurs during the developmental period of early adolescence. Mixed findings exist across the literature on the effects of transition on student adjustment outcomes. This has led to an understanding amongst researchers and educators that the effects of transition are not uniform. Treating young adolescents as a homogeneous group might be extremely misleading.Much of the transition literature in early adolescence has been concentrated on typically developing students. Students with disabilities /chronic ill health conditions and at a social disadvantage have been excluded in cohort and longitudinal investigations. Thus, gaps exists in the understanding of factors that may promote or limit positive school adjustment, especially for those with social or health related issues, some of which have been addressed in this study.The overall aim of this study was to determine the personal and contextual factors that affect adjustment outcomes of all mainstream students including those with disabilities and chronic illness and students at a social disadvantage, as they transition from primary to secondary school in Western Australia. Six study objectives were described, in order to address the aim. Student adjustment in this study was operationalised in terms of academic, emotional-behavioural, social, and participatory dimensions. Therefore, the following outcomes were included: academic competence; emotional and behavioural difficulties; sense of self-worth; school belonging; loneliness and social dissatisfaction; and participation in school extra-curricular activities (e.g., social-leisure, civic, and creative pursuits).A longitudinal study design was used. Two cohorts of participants (those making the transition from primary to secondary school during the academic year 2006/2007, and 2007/2008) were followed. At pre-transition, data from 395 students from a representative range of 45 feeder primary schools were retrieved. Post-transition data from two hundred and sixty six participants from 81 secondary schools across metropolitan and regional Western Australia were collected. Cross-informant data from stakeholders (i.e., parents, teachers and students) were retrieved using psychometrically robust measures.A social-ecological and developmental systems theoretical framework guided the research, which recognized the interdependence of individual characteristics within changing personal, family, school, and peer-group contexts (Bronfenbrenner & Morris, 1998; Brooks-Gunn, Peterson, & Eichorn, 1985; J. S. Coleman & Hendry, 1999). Assumptions about key influencing factors identified in the literature to influence student adjustment in school were tested, using a series of hierarchical linear regression models. The findings of the study confirm four main issues:1. At multivariate level, students‟ gender, health status, and the SES-level of their household influenced adjustment outcomes to a varying degree, depending on: the adjustment outcome under review; the timing of the analysis (i.e., whether it was before or after transition, or longitudinal); and the associated personal and contextual factors considered in each analysis;2. Combinations of personal and contextual factors were found to predict student adjustment outcomes in primary school;3. Longitudinally, primary level combinations of factors had reduced predictive power in explaining secondary school adjustment outcomes; and4. Models that took into account the contribution of previous adjustment in primary school, the replica primary school model (primary school model with corresponding secondary level factors) and factors unique to secondary school, best explained adjustment outcomes in secondary school.Most of the personal and contextual predictors of adjustment can be modified to promote adjustment. Future longitudinal research that tracks mainstream students along the educational continuum is required to identify whether there are any additional personal and contextual factors that take on prominence in the later years of school.